Philippe : gay magazine ; vanaf (1982) : New men of Philippe ; vanaf (1982) dec : Gay Men. (Paris : Silver Taurus Productions, 1980)
Fonds Suzan Daniel (FSD)
Periodiciteit : maandelijksRedactie : 33 rue de Liège, 75008 Paris
Frans
Periodiek